(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
In this article, Utkir Khoshimov is known not only as a bright star of Uzbek literature, but also as a prose writer, dramatist and public figure who played an important role in modern writing. it is revealed that he chose the method.